Impact of Tremor on Upper Limb Function in Parkinson’s Disease: An Cross-sectional Correlational Study - Nagarjuna Narayanasetti; Kshitija Bansal; Annie Thomas (Journal of Clinical and Diagnostic Research)
Introduction: A common symptom of Parkinson’s Disease (PD) is tremor, which, in combination with motor block termed ‘freezing’, acts as a major disabling factor for Upper Extremity (UE) function in people with PD. Aim: To determine the correlation between tremor and upper limb function in PD patients. Materials and Methods: A hospital-based cross-sectional correlational study was conducted over one year at Sri Krishna Neuro and General Hospital, Kasibugga, Andhra Pradesh, India. Thirty primary PD patients aged 40-60 years were enrolled, following inclusion criteria. Tremors were evaluated using the Fahn-Tolosa-Marín tremor rating Scale (FTMS) and Bain and Findley Tremor (BFT) for Activities of Daily Living (ADL). Hand function was assessed using the 9-Hole Peg Test (9HPT) for the Dominant Side (DS) and Non Dominant Side (NDS). Spearman’s correlation, with p-value≤0.05 considered statistically significant, was used for analysis. Results: The mean age of the 30 patients was 56.5±3.83 years; 21 (70%) were males and 9 (30%) were females. The median FTMS total score was 109, with a median severity score of 75.7; the interquartile ranges (IQRs) were 4.75 and 3.30, respectively. Median 9HPT scores were 25.2 (DS) and 27.2 (NDS) and the median BFT score was 71; IQRs were 6.79, 6.87 and 2.75, respectively. Spearman’s correlation showed no significant correlation between FTMS and 9HPT scores, but a moderate correlation (r=0.46) was observed between FTMS and BFT scores (p-value<0.05). Conclusion: Tremor severity (FTMS) was not correlated with hand function. However, a link was identified between tremor and tremor-related ADLs. Further research exploring the relationship between non motor symptoms and motor or cognitive impairment and reduced quality of life associated with PD, is warranted.